Analysis of Palm Oil Price in Southeast Asia - Dwi Lestari; Shanty Oktavilia (AFEBI Economic and Finance Review, 2020)
This study aimed to analyze some factors influencing fluctuations of palm oil (CPO) prices in 3 (three) countries in Southeast Asia. This study analyzes the factors that influence domestic CPO prices from the supply and demand side. International CPO prices, coconut oil prices, and CPO consumption are factors that influence domestic CPO price fluctuations from the demand side, while CPO production is a factor affecting domestic CPO price fluctuations from the supply side. This study uses a quantitative method, where the type of data used in this study is panel data taken from 3 countries, namely Indonesia, Malaysia, and Thailand from 1998-2019. The data were analyzed using multiple linear regression, where the variables used included domestic CPO prices, international CPO prices, coconut oil prices, CPO production, and CPO consumption as independent variables. This study shows that all the independent variables significantly affect the domestic CPO price variable, except for the CPO consumption variable, and all the independent variables have a positive effect on the domestic CPO price variable, except for the CPO production variable. The international CPO price variable is the most dominant in influencing domestic CPO price fluctuations.